Desenvolvimento docente: avaliação de uma experiência em um curso de Medicina (Teacher development: evaluation of an experience in a Medical course) - Almeida, Maria Tereza Carvalho; Maia, Fernanda Alves; Machado, Maria das Mercês Borém Correa; Souza, Filipe Alves; Silva, Victor Bruno da; Carvalho, Mateus Almeida de; Rodrigues Neto, João Felício (Revista Eletrônica de Educação, 2019)
The objective of this study was to evaluate the actions offered in the Teacher Development Program from the perceptions of the teachers of the medical course of a public university that has been working with active teaching and learning methods since 2002. After each action of the program, an evaluation instrument was applied to the participants, and the answers were submitted to content analysis and then organized into three categories: infrastructure and logistics, the teaching-learning strategies and the developed content. Teachers highlight the importance of organization and planning of activities and the environment in which these actions are developed; they emphasize the importance of using teaching–learning strategies that allow greater re?ection on own practice and the integration of theory and practice. They point out that the themes proposed were timely and necessary, they recognize the importance of being in development, they talk about the motivation from the experiences lived. It is concluded that the Teacher Development is a process through which the teacher is in transformation, through a conscious and constant reflection of his own practice. This process can be promoted by institutional investments and by the regulatory mechanisms of institutions, constituted of an evaluation referenced in objective indicators, consistent with the goals to be achieved. In this sense, it is necessary to invest in permanent education, because long-term programs allow the development of the teacher´s and the institution´s needs. Resumo O objetivo deste estudo foi avaliar as ações oferecidas em um Programa de Desenvolvimento Docente a partir da percepção dos professores do curso de medicina de uma universidade pública que utiliza métodos ativos de ensino-aprendizagem desde 2002. Após cada ação do programa, um instrumento de avaliação foi aplicado aos participantes, e respostas foram submetidas à análise do conteúdo e em seguida foram organizadas em três categorias: infraestrutura e logística, estratégias de ensino-aprendizagem utilizadas, e conteúdo desenvolvido. Os professores destacam a importância da organização e planejamento das atividades e do ambiente em que essas ações se desenvolveram; Enfatizam a importância de utilizar estratégias de ensino-aprendizagem que possibilitem maior reflexão sobre a própria prática e a integração da teoria e a prática. Apontam que os temas propostos foram oportunos e necessários, reconhecem a importância de estarem em desenvolvimento, falam sobre a motivação a partir das experiências vivenciadas. Conclui-se que o Desenvolvimento Docente é um processo pelo qual o professor está em transformação, por meio de uma re?exão consciente e constante de sua própria prática. Esse processo pode ser promovido pelos investimentos institucionais e pelos mecanismos reguladores das instituições constituídos por uma avaliação referenciada em indicadores objetivos, coerentes com as metas a serem alcançadas. Nesse sentido, é necessário investir na educação permanente, pois os programas em longo prazo permitem trabalhar as necessidades do professor e da instituição. Resumen El objetivo de este estudio fue evaluar las acciones ofrecidas en un Programa de Desarrollo Docente a partir de la percepción de los profesores del curso de medicina de una universidad pública que utiliza métodos activos de enseñanza - aprendizaje desde 2002. Después de cada acción del programa, un instrumento de evaluación se aplicó a los participantes, y las respuestas se sometieron al análisis del contenido y luego se organizaron en tres categorías: infraestructura y logística, estrategias de enseñanza - aprendizaje utilizadas, y contenido desarrollado. Los profesores destacan la importancia de la organización y planificación de las actividades y del ambiente en que esas acciones se desarrollaron; Enfatizan la importancia de utilizar estrategias de enseñanza - aprendizaje que posibiliten una mayor reflexión sobre la propia práctica y la integración de la teoría y la práctica. Se señalan que los temas propuestos fueron oportunos y necesarios, reconocen la importancia de estar en desarrollo, hablan sobre la motivación a partir de las experiencias vivenciadas. Se concluye que el Desarrollo Docente es un proceso por el cual el profesor está en transformación, por medio de una re?exión consciente y constante de su propia práctica. Este proceso puede ser promovido por las inversiones institucionales y por los mecanismos reguladores de las instituciones constituidos por una evaluación referenciada en indicadores objetivos, coherentes con las metas a ser alcanzadas. En este sentido, es necesario invertir en la educación permanente, pues los programas a largo plazo permiten trabajar las necesidades del profesor y de la institución. Keywords: Educational development, Medical education, Professional development, Qualitative research. Palavras-chave: Desenvolvimento e educação, Formação médica, Desenvolvimento profissional, Pesquisa qualitativa. Palabras claves: Desarrollo y educación, Formación médica, Desarrollo profesional, Investigación cualitativa. References ABID, Kauser. Faculty development: a need in time for educators in healthcare. J Pak Med Assoc, v. 63, n. 4, p. 428-431, Apr., 2013. ALMEIDA, Maria Tereza Carvalho; BATISTA, Nildo Alves. Ser docente em métodos ativos de ensino-aprendizagem na formação do médico. Rev Bras Educ Med, v. 35, n. 4, p. 468-476, julho, 2011. ALMEIDA, Maria Tereza Carvalho; MAIA, Fernanda Alves; BATISTA, Nildo Alves. Gestão nas escolas médicas e sustentabilidade dos programas de desenvolvimento docente. Avaliação: Revista da Avaliação da Educação Superior, v. 18, n. 2, p. 299-310, jul., 2013. ANDERSON, Winston A. et al. Changing the culture of Science Education at research universities. Science Education, v. 331, p.152-153, Jan., 2011. ARMSTRONG, Elizabeth G.; BARSION, Sylvia J. Creating “Innovator’s DNA” in Health Care Education. Academic Medicine, v. 88, n. 3, p. 342-348, Mar., 2013. ARMSTRONG, Elizabeth G.; DOYLE, Jennifer; BENNETT, Nancy L. Transformative professional development of physicians as educators: assessment of a model. Academic Medicine, v. 78, n. 7, p. 702-708, Jul., 2003. AUSUBEL, David Paul. A aprendizagem significativa: a teoria de David Ausubel. São Paulo: Moraes, 1982. BALMER, Dorene F.; RICHARDS, Boyd F. Faculty development as transformation: Lessons learned from a process-oriented program. Teaching and learning in medicine, v. 24, n. 3, p. 242-247, Jul., 2012. BARDIN, Laurence. Análise de conteúdo. 3ed. Lisboa: Almedina, 2004. CATE, Olle Ten et al. Faculty development through international exchange: The IMEX initiative. Medical teacher, v. 36, n. 7, p. 591-595, Jun., 2014. CECIM, Ricardo Burg. Educação permanente em saúde: desafio ambicioso e necessário. Interface – Comunicação, Saúde e Educação, v. 9, n. 16, p. 161-177, fev., 2005. CENTRA, John A. Types of faculty development programs. The Journal of Higher Education, v. 49, n. 2, p. 151-162, 1978. CHOU, Calvin L. et al. The Impact of a Faculty Learning Community on Professional and Personal Development: The Facilitator Training Program of the American Academy on Communication in Healthcare. Academic Medicine, v. 89, n. 7, p. 1051-1056, Jul., 2014. COSTA, Nilce Maria da Silva Campos. Docência no ensino médico: por que é tão difícil mudar?. Rev bras educ méd, v. 31, n. 1, p. 21-30, 2007. DEWEY, John. Experiência e Natureza - Lógica - a Arte Como Experiência - Vida e Educação - Teoria da Vida moral. 2 ed. São Paulo: Abril cultural, 1985. DONABEDIAN, Avedis. Evaluating physician competence. Bulletin of the World Health Organization, v. 78, n. 6, p. 857-860, 2000. EBRAHIMI, Sedigheh; KOJURI, Javad. Assessing the Impact of Faculty Development Fellowship in Shiraz University of Medical Sciences. Arch Iran Med, v. 15, n. 2, p. 79-81, Feb., 2012. FREIRE, Paulo. Pedagogia da autonomia: saberes necessários à prática educativa. São Paulo: Paz e Terra, 1996. GADAMER, Hans Georg. Verdade e Método: traços fundamentais de uma hermenêutica filosófica. Petrópolis: Vozes, 1999. HABERMAS, Jurgen. Conhecimento e interesse. Rio de Janeiro: Ed. Zahar, 1987. KIRKPATRICK, Donald L. Como implementar os quatro níveis de avaliação de treinamento de equipes: um guia prático. 1 ed, Rio de Janeiro: Artmed, 2010. KNIGHT, Amy M. et al. Long?Term Follow?Up of a Longitudinal Faculty Development Program in Teaching Skills. Journal of general internal medicine, v. 20, n. 8, p. 721-725, Aug., 2005. MOORE, Philippa. Logros más alla de los objetivos: evaluación cualitativa de un programa de formación en educación médica. Revista médica de Chile, v. 142, n. 3, p. 336-343, mar., 2014. MORAHAN, Page S.; FLEETWOOD, J. Do we really value what our faculty do? Academic Physician & Scientist, p. 7-9, Sep.-Oct., 2009. NÓVOA, António. Formação de professores e profissão docente. Lisboa: Publicações Dom Quixote. Cap. 1, p. 1-27. 1992. PELIZZARI, Adriana et al. Teoria da aprendizagem significativa segundo Ausubel. Revista PEC, v. 2, n. 1, p. 37-42, jul., 2002. PERRON, Noelle Junod et al. Impact of a faculty development program for teaching communication skills on participants’ practice. Postgraduate medical journal, v. 90, n. 1063, p. 245-250, Apr., 2014. SARIKAYA, Ozlem et al. The impact of a faculty development program: evaluation based on the self-assessment of medical educators from preclinical and clinical disciplines. Advances in physiology education, v. 34, n. 2, p. 35-40, Jun., 2010. SCHÖN, Donald. A. Formar professores como profissionais reflexivos. In: NÓVOA, Antônio. Os professores e sua formação. Lisboa: Dom Quixote. v. 2, p. 77-91, 1992. SIMPSON, Deborah et al. Fifteen years of aligning faculty development with primary care clinician–educator roles and academic advancement at the Medical College of Wisconsin. Academic Medicine, v. 81, n. 11, p. 945-953, Nov., 2006. SINGH, Tejinder et al. Impact of a fellowship program for faculty development on the self-efficacy beliefs of health professions teachers: A longitudinal study. Medical teacher, v. 35, n. 5, p. 359-364, Jun., 2013. STEINERT, Yvonne et al. A systematic review of faculty development initiatives designed to improve teaching effectiveness in medical education: BEME Guide No. 8. Medical teacher, v. 28, n. 6, p. 497-526, Sep., 2006. STEINERT, Yvonne et al. Faculty development as an instrument of change: A case study on teaching professionalism. Academic Medicine, v. 82, n. 11, p. 1057-1064, Nov., 2007. WILKERSON, LuAnn; IRBY, David M. Strategies for improving teaching practices: a comprehensive approach to faculty development. Academic Medicine, v. 73, n. 4, p. 387-396, Apr., 1998.